REFLEKSI NILAI ADAT DAN IDENTITAS TRADISI MAPPASIKARAWA PADA PERNIKAHAN MASYARAKAT SULAWESI SELATAN - Ahmad; Ahmad Yani (Istiqra: jurnal hasil penelitian, 2026)
This study offers a novel contribution to cultural studies and communication by integrating cultural semiotics analysis with an ethnopedagogical perspective to examine the Mappasikarawa tradition holistically—not merely as a ceremonial ritual, but as a symbolic communication system that embodies the construction of collective identity in South Sulawesi society. Unlike previous research, which generally approached Bugis-Makassar marriage traditions from the standpoint of customary law or purely ethnographic description, this study specifically investigates how customary values embedded in gestures, ritual sequences, and the meaning of the first touch (Mappasikarawa) function as a medium for transmitting cultural identity across generations amid modernization and social change. Social facts reveal that in the era of digitalization, an anomaly has emerged where communal traditions are frequently reduced to visual commodities, thereby risking the disconnection of the younger generation from their philosophical roots. Employing a qualitative approach that combines communication ethnography, cultural semiotics (Peirce and Lotman), and symbolic interactionism (Mead), this research finds that Mappasikarawa gestures contain informal cultural pedagogy transmitting the doctrines of siri’ na pacce, lempu’, and getteng. The nonverbal signs within this ritual operate within a semiosphere uniting the sacred and profane realms, while integrating Islamic law (‘urf shahih and maqashid al-syariah) with local wisdom. The study’s conclusions yield understanding of cultural resilience among indigenous communities of South Sulawesi in preserving identity, while positioning Mappasikarawa as essential multicultural education instrument for globalization challenges.